Spread apple scab in the western region of Ukraine - Skoreyko, A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The results of the survey to identify apple orchard pathogen destruction Venturia inaequalis in Chernivtsi and Zakarpattia regions. Minimum scab lesions observed in the Chernovtsy region Khotyn district (Farm «Mayak») on the varieties Golden, Glory winner, Idared.